Determination of Financial Distress In Food and Beverage Subsector Companies - Stevany; Dini Hariyanti; Jakaria (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to determine the influence of profitability, leverage, good corporate governance, gender diversity, political connections, and consumer protection policies on financial difficulties in food and beverage companies listed on the Indonesia Stock Exchange. The sample was collected using purposive sampling, with a total of 27 companies meeting the criteria during the research period. The analysis method used was panel data regression processed using EViews software. The results of this study indicate that profitability has a positive effect on financial distress, meaning that companies with high profits may face certain financial pressures that may be caused by large investments or aggressive expansion. Meanwhile, leverage, good corporate governance, and gender diversity were found to have a negative impact on financial distress, indicating that cautious financing structures, sound managerial practices, and diversity in leadership can reduce the likelihood of a company experiencing financial distress. On the other hand, political connections and consumer protection policies did not show a significant impact on companies' financial difficulties, suggesting that these external factors may not be the primary determinants of the financial condition of food and beverage companies. These findings are expected to contribute to academic literature and serve as considerations for management and stakeholders in making strategic decisions to avoid potential bankruptcy risks in the future.